Quality of web-based information for osteoarthritis: a cross-sectional study. Issue 3 (September 2018) - Barrow, A.; Palmer, S.; Thomas, S.; Guy, S.; Brotherton, J.; Dear, L.; Pearson, J.
Abstract: Background: Osteoarthritis (OA) is a chronic condition that affects over 8.75 million people in the UK. Approximately 43% of people in the UK search for health and medical information online. However, health information on the internet is of variable quality. Research into the quality of online OA information is dated and there is a need to evaluate the existing information. Objectives: To assess the quality of websites which provide educational information for patients with OA. Design: Electronic cross-sectional survey. Methods: The search term 'osteoarthritis' was entered into the five popular UK-based search engines in order to identify 50 unique websites. These websites were appraised by two assessors using criteria developed from the available literature and recent guidelines of the National Institute of Health and Care Excellence. The appraisal considered the general quality of the website and OA-specific content. Results: Most of the websites evaluated (34/50, 68%) scored more than half of the maximum available quality score (max score 59). The median total score was 41. For general quality of the website, the median score was nine (range three to 16, out of 16), and for OA-specific content, the median score was 31 (range two to 43, out of 43). Websites of higher quality were created more recently, disclosed sources of information, had external seals of approval and directed the reader on to other relevant websites. Conclusions: The internet is a potentially useful tool for educating and empowering healthcare consumers. The websites evaluated were generally of a 'high' standard; however, there was wide variation in the quality of information.